Artificial immune network model based controller for vibration suppression of flexible structures - Md. Salleh, Salihatun; Tokhi, M. Osman; Toha, Siti Fauziah (2010)
This paper presents a model based controller with immune inspired algorithm to suppress flexible plate vibration. Artificial immune network (AiNet) algorithm with real-valued random initialisation of antibodies is considered to optimise the system model for use in active vibration controller development in a single-input and multi-output (SIMO) configuration. The AiNet model based controller thus developed shows the capability of the approach with relatively better accuracy in comparison to using real-coded genetic algorithm. The simulation results also reveal improvement in vibration reduction and less computational time.